The Syndrome MIH Systemic Impact in Children and Adolescents: Relevance Area - Marinela Pasareanu; Roxana Mihaela Mocanu; Adriana Balan (Romanian Society of Oral Rehabilitation, 2012)
The aim of our study is to monitor permanent incisors and molars syndrome of hypomineralization in (MIH) in a pediatric population in Iaşi, using evaluation procedures and criteria established by EAPD. Study group consisted of 334 children (169 girls and 165 boys), divided into two - 43 children with developmental defects of enamel and 291 children without developmental defects of enamel. The prevalence of developmental enamel defects was 10.28% for permanent incisors and 4.26% to permanent molars; MIH syndrome prevalence in the studied casuistry was 14.54%. We notice the presence of multiple lesions 3.3% - opacity, hypoplasia or stains, and in 64.4% of cases the defect extension less than one third of the tooth surface. The risk of being affected more molars grow at a rate of 47% where it affects more incisors.